THE ROLE OF PAI CURRICULUM MANAGEMENT IN INCREASING STUDENTS' LEARNING MOTIVATION AT MODERN PONDOK DARUL FALAH ENREKANG SMP, ENREKANG DISTRICT - Lalunggaeng, Imba; Sumiati, Sumiati; Mawardi , Amirah; Malli, Rusli (Jurnal Konseling Pendidikan Islam, 2023)
This study aims to analyze the role of Islamic Religious Education (PAI) curriculum management in increasing students' learning motivation at SMP Pondok Modern Darul Falah Enrekang. In addition, this research seeks to identify the factors that influence students' learning motivation within the context of Islamic education in pesantren and provide recommendations on strategies that can be applied in PAI curriculum management to enhance learning motivation, especially in the digital era. The research method used is a qualitative approach with a case study design. Data were collected through semi-structured interviews with the school principal, PAI teachers, and students, classroom observations during PAI lessons, and document analysis related to the curriculum. The data were analyzed interactively through the processes of data collection, reduction, display, and conclusion drawing. The results show that PAI curriculum management plays a significant role in fostering students' learning motivation by integrating religious and academic aspects, thus creating a meaningful and relevant learning environment for students. Factors such as interactive teaching methods, the relevance of learning materials to everyday life, and peer support were found to be important elements influencing students' learning motivation. The study also identifies that the use of digital technology in the learning process, as well as curriculum flexibility that allows teachers to adjust materials to meet students' needs, can further enhance learning motivation. Based on these findings, the research recommends increasing the use of digital tools, providing more autonomy for teachers in designing lessons and implementing continuous evaluation to create a more dynamic and motivating learning environment.